2010
DOI: 10.1097/mph.0b013e3181cf7ef3
|View full text |Cite
|
Sign up to set email alerts
|

External Auditory Canal and Middle Ear Relapse of Acute Promyelocytic Leukemia Treated With Arsenic Trioxide

Abstract: Extramedullary involvement occurs infrequently in acute promyelocytic leukemia and is said to be more common after treatment with all-trans retinoic acid. We describe a 9-year-old girl who had an isolated external auditory canal and middle ear relapse after treatment with all-trans retinoic acid and chemotherapy. A patient with cytogenetically and molecularly confirmed acute promyelocytic leukemia developed isolated extramedullary relapse in the auditory canal and middle ear 4 years and 9 months after initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…3). A recent review of external auditory canal and middle ear relapse found 23 similar cases previously described, with most cases occurring within the first 2 years after diagnosis [17]. While the reason for extramedullary relapse is not certain, several theories exist.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…3). A recent review of external auditory canal and middle ear relapse found 23 similar cases previously described, with most cases occurring within the first 2 years after diagnosis [17]. While the reason for extramedullary relapse is not certain, several theories exist.…”
Section: Discussionmentioning
confidence: 94%
“…Treatment of extramedullary relapse has not been thoroughly studied, but it appears that arsenic trioxide is useful not only in medullary relapse, but in extramedul-lary relapse as well. This may be due to arsenic's ability to deposit well in epidermal tissues [17].…”
Section: Discussionmentioning
confidence: 99%
“…EMR, as in our patient, is rarely reported in patients treated for APL [ 5 , 6 ]. EMR can occur in the CNS [ 5 - 11 ], skin [ 5 , 6 , 9 , 12 ], middle ear [ 5 , 9 , 11 , 13 ], lung [ 5 ], pleura [ 14 ], sites of vascular access [ 12 ] and sites of bone marrow aspiration and biopsy [ 12 ]. However, CNS is the predominate site of EMR with an estimated risk of 0.6 to 2% [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reported cases were treated with intrathecal chemotherapy with or without radiation therapy [ 6 , 8 , 10 ]. ATRA, ATO and/or chemotherapy were also used to treat systemic disease when present simultaneously [ 11 , 13 , 19 - 21 ]. Unfortunately, ATRA has limited penetration to CNS and therefore, is used primarily to treat systemic disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic trioxide (As 2 O 3 ) has been successfully used to treat leukemia [11][13] and is active in several solid tumors, including gastric cancer [14]. The mechanism of action of As 2 O 3 includes affecting the activities of Akt, JNK kinases, NF-κB, glutathione, calcium signaling, reactive oxygen species(ROS), and caspases, as well as pro- and anti-apoptotic proteins [15]–[18].…”
Section: Introductionmentioning
confidence: 99%